A Higher Initial Tensioning Force of an ACL Graft Results in a Higher Graft Force After Screw Fixation Irrespective of the Screw Diameter: A Biomechanical Study. Issue 14 (December 2021) - Kayaalp, M. Enes; Collette, Robert; Kruppa, Philipp; Flies, Anne; Schaser, Klaus-Dieter; Wulsten, Dag; Duda, Georg N.; Becker, Roland; Kopf, Sebastian
Background: The intra-articular graft force (IAGF) in anterior cruciate ligament reconstruction decreases quickly over the first hours after surgery. Nevertheless, little is known about whether the initial extra-articular tensioning force (EATF) and screw diameter affect the graft force after fixation. Purpose: To investigate the effects of different EATFs on the IAGF of a soft tissue graft fixated via a bioabsorbable interference screw over 100 minutes after fixation and to evaluate the effects of different screw diameters within 1 mm of the tunnel width during this process. Study Design: Controlled laboratory study. Methods: In this biomechanical study, a porcine quadruple-strand soft tissue graft was inserted into the tibial anterior cruciate ligament tunnel. On the extra-articular side, 3 loads were applied during retrograde insertion of the bioabsorbable interference screw (6, 7, and 8 mm): 20 N, 80 N, and maximum manual EATF (Nmax ). Nine study groups consisting of 10 tibiae each were created to test the effects of different EATFs and screw sizes. The IAGF was measured up to 100 minutes after the EATF was released. Results: An EATF ≥80 N resulted in a larger IAGF for all screw sizes at 100 minutes. There were no significant associations between the IAGF at 100 minutes and different screw diameters. Inserting the tibial screw significantly increased the IAGF in all groups, with the exception of Nmax applied in groups with 7- or 8-mm screws. When compared with the end of screw insertion, after the release of the EATF, the IAGF dropped by 55% to 77 % at 100 minutes. Conclusion: An initial EATF ≥80 N is associated with a significantly larger IAGF at 100 minutes in this cadaveric simulation. The IAGF in soft tissue grafts decreased substantially after the retrograde placement of an interference screw. A recommendation regarding screw diameter with respect to the IAGF cannot be given. Clinical Relevance: To obtain a higher residual graft force after bioabsorbable interference screw fixation, an initial EATF ≥80 N should be applied according to this model. The significant decrease in graft force after the release of the EATF indicates that the reconstructed knee cannot be mechanically stabilized after the surgery.